Cross-cutting public policies - monetary and multidimensional poverty in Colombia (2022)
The phenomenon of poverty in Colombia can be defined as a complex network of intertwined phenomena and factors. The current definitions refer to widely accepted international standards, in which the impossibility of satisfying basic needs is pointed out as the main problem. The special Colombian characteristics make the study of poverty more complex than in other regions, taking into account the cultural change suffered as the national territory is traveled. Poverty is a phenomenon that does not have a single origin and varies according to gender, age, social status, geographic location, education and, in general, access to decent conditions that allow improving the individual's quality of life; hence the importance of generating results to be social variables with the purpose of generating a public policy that minimizes the social systems in which we live, and on the contrary, tends to dignify the life of each citizen according to the social contract that has been ratified throughout history. The State role is the protagonist and cannot be seen outside the same problem, since it is the obligation of the public administration to create opportunities for continuous improvement through plans, programs and projects.